Public Policy and National Defense in Border Area Management: An Analysis of National Security Strategy - Wisnu Saputro; Asep Adang Supriyadi; Bambang Kustiawan; Robby Mochammad Taufik; Guntur Eko Saputro; Ghazalie Ghazalie (LPPM Institut Pendidikan Nusantara Global, 2026)
Border area management plays a strategic role in strengthening state sovereignty and supporting an adaptive national defense system. This article analyzes the interconnection between public policy and national defense strategies in the context of Indonesia’s border management, using a qualitative-descriptive approach based on literature review and theoretical analysis. In addressing multidimensional threats such as infiltration, smuggling, terrorism, and geopolitical crises, border management must be integrative, adaptive, and sustainable. The analysis reveals that public policy holds a central role in shaping governance frameworks that support infrastructure development, basic services, and community empowerment in border regions. Meanwhile, national defense strategies must adopt advanced technologies such as drones, data-based surveillance systems, and artificial intelligence (AI) to enhance threat detection and response effectiveness. Synergy between central government, local authorities, and local communities through a multilevel governance approach proves critical in establishing a responsive border management system. Furthermore, the integration of economic, technological, and defense dimensions forms the foundation for transforming border areas into not only defense zones but also centers of economic growth and strategic diplomacy. This article recommends strengthening data-driven policies, strategic innovation, and international cooperation to build a robust, inclusive, and globally competitive national security system